Introduction toReview of Financial StudiesConference on Market Frictions and Behavioral Finance - Heaton, John; Korajczyk, Robert (Review of Financial Studies, 2002)
A significant amount of research by financial economists over the last few decades has attempted to understand various anomalous or puzzling empirical observations taken from financial markets.1 These range from the equity premium puzzle at the aggregate level [see, e.g., Grossman and Shiller (1982) and Mehra and Prescott (1985)], to the small-firm effect [see, e.g., Banz (1981) and Fama and French (1992)], to momentum in returns [see, e.g., De Bondt and Thaler (1985) and Jegadeesh and Titman (1993)], to postevent abnormal returns [see, e.g., Latane and Jones (1977) and Ritter (1991)] at the level of individual stock and portfolio returns. In each case these empirical puzzles are identified by finding portfolios with average returns that are high relative to their risk as measured by the covariance of the returns with the market portfolio, as in the capital asset pricing model (CAPM), or with aggregate consumption, as in the consumption-based CAPM. If the assumptions about market structure and the behavior of agents justifying the models are correct, then return observations imply that agents should trade to take advantage of the observed patterns in returns. There have been three types of explanations put forward for why agents don’t take advantage of the anomalies.